Rodent pollination in Androcymbium latifolium (Colchicaceae) - Kleizen, Ciara (Department of Biological Sciences, 2017)
The repeated discovery of rodent pollination (therophily) has led to the concept of a rodent pollination syndrome. The adaptive plant traits that characterize this syndrome include flowers packed tightly into geoflorous and cryptic inflorescences, nocturnal anthesis and production of copious amounts of sugar-rich nectar and pollen as well as a musky odour. Androcymbium latifolium (Colchicaceae), a geophyte that occurs in the semiarid Succulent karoo region of South Africa, exhibits several of the therophilous traits. Experiments were conducted investigating the hypothesis that this species is rodent pollinated. Several lines of evidence were found to support this hypothesis. These include: the almost exclusive presence of A. latifolium pollen in the scats of live-trapped Aethomys namaquensis rodents and in the fuschin gelatine swabs from the rostrum area of the rodents; and observations of captive A. namaquensis individuals foraging for nectar non-destructively in A. latifolium inflorescences. The exclusion of rodents from inflorescences resulted in a significant decrease in seed set compared to control plants. This result indicated that rodents do contribute to pollination success of A. latifolium, however, in the absence of rodents, the flowers self-pollinate, indicating a facultative selfing strategy. Therefore, A. latifolium displays an opportunistic life history attracting rodents to the sugar-rich nectar when other food sources are scarce. This is supported by the observation that the seed set of A. latifolium decreases as the distance from the rodents nesting site increases. This study presents substantial evidence for therophily in A. latifolium, making this species the first species in the family Colchicaceae, and the second geophyte in the world to be rodent pollinated.